2021
DOI: 10.3390/cells10102651
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin Is a Positive Allosteric Modulator of κ-Opioid Receptors but Not δ-Opioid Receptors in the G Protein Signaling Pathway

Abstract: Oxytocin (OT) influences various physiological functions such as uterine contractions, maternal/social behavior, and analgesia. Opioid signaling pathways are involved in one of the analgesic mechanisms of OT. We previously showed that OT acts as a positive allosteric modulator (PAM) and enhances μ-opioid receptor (MOR) activity. In this study, which focused on other opioid receptor (OR) subtypes, we investigated whether OT influences opioid signaling pathways as a PAM for δ-OR (DOR) or κ-OR (KOR) using human e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…The influence of OT on other systems appears to be widespread, as it not only interacts with 5-HT and DA, but also directly influences CRH and opioid activity. To list a few examples: OTRs expressed on serotonin (5-HT) terminals in the NAc are critical for social motivation (Dölen et al, 2013), OTR activation in the VTA is necessary for social reward in male and female Syrian hamsters (Borland et al, 2019), OT modulates HPA activity and CRH release via interaction with GABA-A receptors in the PVN (Smith et al, 2016), and OT binds to Mu opioid receptors as a positive allosteric modulator and directly influences anxietylike behavior associated with chronic pain (Meguro et al, 2018;Miyano et al, 2021). Finally, the social salience hypothesis of OT proposes that OT regulates the salience of social stimuli and increases sensitivity to social cues depending on context and individual factors (reviewed in Shamay-Tsoory and Abu-Akel, 2016).…”
Section: Oxytocinmentioning
confidence: 99%
“…The influence of OT on other systems appears to be widespread, as it not only interacts with 5-HT and DA, but also directly influences CRH and opioid activity. To list a few examples: OTRs expressed on serotonin (5-HT) terminals in the NAc are critical for social motivation (Dölen et al, 2013), OTR activation in the VTA is necessary for social reward in male and female Syrian hamsters (Borland et al, 2019), OT modulates HPA activity and CRH release via interaction with GABA-A receptors in the PVN (Smith et al, 2016), and OT binds to Mu opioid receptors as a positive allosteric modulator and directly influences anxietylike behavior associated with chronic pain (Meguro et al, 2018;Miyano et al, 2021). Finally, the social salience hypothesis of OT proposes that OT regulates the salience of social stimuli and increases sensitivity to social cues depending on context and individual factors (reviewed in Shamay-Tsoory and Abu-Akel, 2016).…”
Section: Oxytocinmentioning
confidence: 99%
“…In an in vitro study, the neuropeptide oxytocin enhanced the activity of several μOR agonists, exhibiting probe dependence, without having any agonist effect on its own, a profile consistent with μOR PAMs [104] . A more recent study suggested that oxytocin also acts as a biased PAM towards the G‐protein pathway at the κOR but not the δOR [105] . Other recently discovered allosteric ligands of μOR, through combination of in vivo and in silico studies, include compound 1 , an allosteric agonist and compound 2 , a PAM [106] …”
Section: Allosteric Ligandsmentioning
confidence: 91%
“…[104] A more recent study suggested that oxytocin also acts as a biased PAM towards the G-protein pathway at the kOR but not the δOR. [105] Other recently discovered allosteric ligands of μOR, through combination of in vivo and in silico studies, include compound 1, an allosteric agonist and compound 2, a PAM. [106] Overall, structurally dissimilar compounds have proven able to modulate the OR activity through binding to its allosteric site.…”
Section: Allosteric Ligandsmentioning
confidence: 99%
“…In addition, OT can indirectly influence the function of other receptors. For example, OT serves as a positive allosteric regulator of opioid receptors [ 68 , 69 ]. In addition, OT regulates gaseous transmitters, including hydrogen sulfide (H 2 S), nitric oxide (NO) and CO 2 , with generally protective effects on tissues throughout the body [ 26 , 27 ].…”
Section: The Oxytocin Receptormentioning
confidence: 99%